Polyoxometalate@Periodic mesoporous organosilicas as active materials for oxidative desulfurization of diesels - Ribeiro, Susana (2020)
Novel material catalysts based in the active zinc-substituted polyoxotungstate ([PW11Zn(H2O)(39)](5-), abbreviated as PW11Zn) were efficiently used in the oxidative desulfurization of real and model diesels. These active catalytic center was strategically immobilized in a less hydrophilic periodic mesoporous organosilicas (PMOs), containing ethane-bridge (PMOE) and benzene-bridge (PMOB) walls, functionalized with (3-aminopropyl)triethoxysilane (aptes). The efficiency of the novel catalytic composites (PW11Zn@aptesPMOE and PM11Zn@aptesPMOB) was studied under oxidative desulfurization system (CODS) without the presence of an extraction solvent and also using a biphasic (diesel/extraction solvent) oxidative desulfurization system (ECODS). Both composites presented higher desulfurization efficiency under the solvent-free system, reaching ultra-low levels of sulfur compounds after only 1 h and using low ratio of H2O2/S = 4. The catalysts could be recycled without loss of activity for ten consecutive cycles. However, after the first desulfurization cycle complete desulfurization was achieved within only 30 min using PW11Zn@aptesPMOE composite. Also, the structure of PW it Zn@aptesPMOE demonstrated to be more stable than PW11Zn@aptesPMOB, probably due to the occurrence of some PW11Zn leaching from the PMOB surface, probably caused by the lower interaction of PW11Zn with the benzene-bridge PMOB wall. The most robust catalyst PW11Zn@aptesPMOE was used to desulfurize a real diesel achieving 75.9% of desulfurization after 2 h. The catalyst was further recycled with success to treat real diesel.